Risk Factors for COVID-19 Adverse Outcomes in ICU Settings of Various Types Repurposed Hospitals - A. A. Avramov; E. V. Ivanov; A. V. Melekhov; R. S. Menzulin; A. I. Nikiforchin (Общая реаниматология, 2023)
Objective: to study the risk factors for COVID-19 adverse outcomes in repurposed hospitals of various types.Material and methods. A retrospective study was conducted in the ICUs of three repurposed hospitals: a municipal hospital, a federal center and a private clinic. Data of 369 patients were analyzed for the period from April to December 2020. Gender, age, BMI, NEWS score, severity of lung damage based on CT quantification, blood gases and pH, patterns of antibiotic administration during hospital stay (all classes and number of antimicrobials, regardless the sequence of administration), patterns of main drugs administration (glucocorticosteroids, lopinavir/ritonavir, tocilizumab/ solilumab, hydroxychloroquine) were evaluated as risk factors. Odds ratios (OR) and 95% confidence intervals (95% CI) were calculated by logistic regression.Results. Patients from repurposed hospitals of various types were distinguishable in terms of distribution by sex, severity of lung damage, administered therapy, blood gases, and the number of antimicrobials used. Mortality rates were 21.8% in the federal center, 41.4% in the private clinic, and 77.2% in the municipal hospital. The most significant risk factors were: the severity of lung damage based on CT quantification (OR=3.694, 95% CI: 1.014–13.455, P=0.048) — in the federal center, patient’s age (OR=1.385, 95% CI: 1.034–1.854, P=0.029) and arterial oxygen tension (OR=0.806, 95% CI: 0.652–0.996) — in the municipal hospital, and patients’ age (OR=2.158, 95% CI: 1.616–2.880, P0.0001), number of antibiotics (OR=1.79, 95% CI: 1.332–2.406, P=0.0001), and blood pH (OR=0.381, 95% CI: 0.261–0.555, P0.0001) — in the private clinic.Conclusion. Patient’s profiles in municipal, federal, and private ICU settings varied significantly in the first wave of the COVID-19 pandemic. Gender distribution and severity of the diseases were found as the most significant differences among them. Clinical outcomes were also different, with the lowest mortality rate in the federal center and the highest in the municipal hospital. Arterial pO₂, blood pH, and the number of antimicrobials used in the course of treatment were the significant risk factors of fatal outcome (in some hospitals).